Growth perfomance of Centella Asiatica (L.) grown on different soilless media in vertical farming - Zakaria, Mohamad Farhan (2015)
Centella asiatica or pennywort belongs to the family of Apiaceae is one of medicinal herbs that has high potential to be commercialized. It has been used as an aid to meditation and listed as one of the Traditional Chinese Medicine (TMC) in China in order to promote faster healing for small wound. On the other hand, due to the increasing population in Malaysia, urban agriculture is being encouraged by the government to the urban population as an alternative way to address the problem of food demand. In this experiment, soilless culture and vertical farming which is part of urban agriculture were used. The purpose of this experiment were to study the growth performance of Centella asiatica grown on various combination of soilless substrates and to determine the best soilless substrates for cultivating Centella asiatica. There were four treatments have been used in this experiment which are ; 100% cocopeat, 70% cocopeat + 30% rice husk, 70% cocopeat + 30% peat moss, and 70% cocopeat + 30% empty fruit bunch. The experiment was laid out in a Randomized Complete Block Design (RCBD) with four replications. Analysis of variance indicated that there were significant differences (P < 0.05) among the treatments in total leaf area, fresh weight and dry weight, relative chlorophyll content, and the macronutrients. The phytochemicals of Centella asiatica was not significantly affected by the combination of substrates. Based on the result, the combination of cocopeat and rice husk produced higher biomass and yield compared to the other treatments.